2010
DOI: 10.1097/eja.0b013e3283312725
|View full text |Cite
|
Sign up to set email alerts
|

Learning fibreoptic intubation with a virtual computer program transfers to ‘hands on’ improvement

Abstract: Self-training in fibreoptic intubation with the VFI software may improve the acquisition of fibreoptic intubation skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 12 publications
0
44
0
1
Order By: Relevance
“…Other studies have shown that training on virtual reality models does improve clinical performance. Boet et al 17 and Park et al 18 have both shown that training on virtual reality simulators for fiber-optic intubation 17 and colonoscopy 18 improved clinical performance. The model studied by Boet et al 13 was very similar to our spine ultrasound model, as their model did not provide immersion or haptic feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that training on virtual reality models does improve clinical performance. Boet et al 17 and Park et al 18 have both shown that training on virtual reality simulators for fiber-optic intubation 17 and colonoscopy 18 improved clinical performance. The model studied by Boet et al 13 was very similar to our spine ultrasound model, as their model did not provide immersion or haptic feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al 13 showed that practicing for two to three hours on a computer-based colonoscopy simulator was effective in transferring skills to live models. In their study looking at the use of virtual simulation in teaching fibreoptic intubation, Boet et al 14 showed that self-training on the virtual fibreoptic intubation software improved the acquisition of fibreoptic intubation skills in 42 undergraduate medical students. Nevertheless, both of these studies involved simulators with a physical component that allowed practice of manual skills.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study 11 involving medical students, who were tested to perform fibreoptic intubation in a mannequin model, after an expert bronchoscopist provided a didactic lecture with, or without, virtual fibreoptic intubation (VFI) software, showed an increased success rate on hands-on practice when the VFI software was used as an adjunct compared to the expert bronchoscopist group alone. Perhaps, a similar teaching method could be recommended when training non-thoracic anaesthesiologists, so the teaching from the expert combined with the CD ROM material could improve the success rate of the placement of DLTs.…”
Section: Limitationsmentioning
confidence: 98%